2018
DOI: 10.3390/molecules23030510
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylcytisine Ameliorates Dextran-Sulfate-Sodium-Induced Colitis in Mice by Inhibiting the Inflammatory Response

Abstract: This study aimed to investigate the anti-inflammatory effects of N-methylcytisine (NMC) in a dextran sulfate sodium (DSS)-induced colitis model and explore its possible mechanisms. Experimental colitis was induced by administering the mice with 5% DSS for 7 days. Different doses of NMC (1, 4 and 16 mg/kg) and 5-aminosalicylic acid (100 mg/kg) were given orally once every day for 7 days. The protective effect of NMC was evaluated using the disease activity index, colon length and results of histopathological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 46 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…As shown in Figure 1, DSS evoked severe inflammation in mice such as a dramatic loss of body weight, colon length shortening from days three to seven compared to control mice, which were consistent with previous publications [19,20]. However, intraperitoneal injection of MMI-0100 (0.5 and 1 mg/kg, i.p.)…”
Section: Resultssupporting
confidence: 91%
“…As shown in Figure 1, DSS evoked severe inflammation in mice such as a dramatic loss of body weight, colon length shortening from days three to seven compared to control mice, which were consistent with previous publications [19,20]. However, intraperitoneal injection of MMI-0100 (0.5 and 1 mg/kg, i.p.)…”
Section: Resultssupporting
confidence: 91%
“…At rest, IκB-α binds to the p50 and p65 subunits of NF-κB. Once microglia are activated, IκB-α is separated and transferred from the cytoplasm to the nucleus, resulting in transcription and expression of inflammatory factors [49]. NF-κB is expressed in nearly all cells and plays an important role in the activation of the M1 microglial phenotype [50].…”
Section: Discussionmentioning
confidence: 99%
“…N -methylcytisine ( 6 ) is also a tricyclic quinolizidine alkaloid isolated from the seeds of traditional Chinese medicines Laburnum anagyroides and Sophora alopecuroides. It has been reported that oral administration of N -methylcytisine (4 and 16 mg/kg of body weight in mice) significantly attenuates the DSS-induced clinical symptoms and pathological damage which are associated with inhibiting colon proinflammatory cytokines through down-regulating NF-κB activation by inhibiting IκB and IKK phosphorylation (Jiao et al, 2018) (Figure 1).…”
Section: Plant-based Alkaloids Against Ibdmentioning
confidence: 99%